2020
DOI: 10.1021/acs.chemmater.0c01258
|View full text |Cite
|
Sign up to set email alerts
|

HgCuPS4: An Exceptional Infrared Nonlinear Optical Material with Defect Diamond-like Structure

Abstract: Infrared nonlinear optical (IR-NLO) crystals possessing excellent comprehensive performance are highly desirable, yet their preparation remains extremely challenging. Particularly, inorganic chalcogenides with diamond-like (DL) structures provide a tunable material platform for their structural design and functional control. In this work, a strategy involving the construction of chalcogenides with DL structures using the strong polarizability of metal cations has been put forward; thus, a quaternary Hg-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 72 publications
8
81
0
Order By: Relevance
“…As Figure b shows, the 0-level IR transparent range of MISP was 0.56–16.4 μm, which was significantly broader than that of state-of-the-art ZnGeP 2 (0.7–12.5 μm), AgGaS 2 (0.5–13 μm), CdSiP 2 (0.58–10 μm), BaGa 4 S 7 (0.35–13.7 μm), BaGa 2 GeS 6 (0.41–11.8 μm), LiGaS 2 (0.32–11.6), LiGaSe 2 (0.37–13.2), LiInS 2 (0.41–12.0), and LiInSe 2 (0.47–13.3). ,, Remarkably, in the 0.7–10 μm region, MISP had good optical transparency (>50%) without absorption, which indicated that it could be effectively pumped using the mature commercial 1.064, 2.090, and 9.6 μm laser source. Two obvious phonon absorption peaks at 10.5 and 11.9 μm were observed, which are common phenomena in chalcogenide and pnictide IR NLO crystals. Significantly, the phonon absorption band was longer that those of ZnGeP 2 (∼9.0 μm), CdSiP 2 (6.7 μm), BaGa 4 S 7 (∼9.0 μm), and BaGa 2 GeS 6 (∼8.0 μm). The phonon spectrum of MISP, determined by Raman scattering on powder samples, are presented in Figure S6a.…”
Section: Resultsmentioning
confidence: 99%
“…As Figure b shows, the 0-level IR transparent range of MISP was 0.56–16.4 μm, which was significantly broader than that of state-of-the-art ZnGeP 2 (0.7–12.5 μm), AgGaS 2 (0.5–13 μm), CdSiP 2 (0.58–10 μm), BaGa 4 S 7 (0.35–13.7 μm), BaGa 2 GeS 6 (0.41–11.8 μm), LiGaS 2 (0.32–11.6), LiGaSe 2 (0.37–13.2), LiInS 2 (0.41–12.0), and LiInSe 2 (0.47–13.3). ,, Remarkably, in the 0.7–10 μm region, MISP had good optical transparency (>50%) without absorption, which indicated that it could be effectively pumped using the mature commercial 1.064, 2.090, and 9.6 μm laser source. Two obvious phonon absorption peaks at 10.5 and 11.9 μm were observed, which are common phenomena in chalcogenide and pnictide IR NLO crystals. Significantly, the phonon absorption band was longer that those of ZnGeP 2 (∼9.0 μm), CdSiP 2 (6.7 μm), BaGa 4 S 7 (∼9.0 μm), and BaGa 2 GeS 6 (∼8.0 μm). The phonon spectrum of MISP, determined by Raman scattering on powder samples, are presented in Figure S6a.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various IR NLO‐active anionic groups, Hg‐based BBUs are very competitive due to several advantages: 1) Hg 2+ cation possesses highly polarizable and deformable electron cloud, which would significantly increase the second harmonic generation (SHG) effect and birefringence; [ 12 ] 2) multiple coordination modes of Hg exist including linear, trigonal‐planar, and tetrahedral geometries, which provide opportunities to construct novel structures. Many Hg‐based IR NLO crystals have been discovered recently in both halides and chalcogenides systems with strong SHG responses and wide bandgaps ( E g ), such as Na 2 Hg 3 Ge 2 S 8 (2.2 × AGS; 2.68 eV), [ 13 ] BaHgSe 2 (1.5 × AGS; 1.56 eV), [ 14 ] SrHgGeSe 4 (4.8 × AGS; 2.42 eV), [ 15 ] CuHgPS 4 (6.5 × AGS; 2.03 eV), [ 16 ] AgHgPS 4 (5.06 × AGS, 2.63 eV), [ 17 ] Cs 2 HgI 2 Cl 2 (1 × KDP; 3.15 eV), [ 18 ] and RbHgI 3 (7 × KDP; 2.56 eV). [ 19 ] Thereby, mixed‐anion [HgQ m X n ] BBUs are expected to exist and perform well.…”
Section: Introductionmentioning
confidence: 99%
“…12 At the beginning of the new century, mercury halogenides and chalcogenides received renewed attention as possible infrared nonlinear optic (NLO) materials suitable for use in the MIR spectral region because: (i) they crystallise in noncentrosymmetric space groups; (ii) show a wide IR transparency; and (iii) possess a large band gap, which can improve the laser-induced damage thresholds. 13 Three different compounds have been reported (HgBrI, Hg 2 BrI 3 and Hg 2 Br 3 I) 14 and the structural parameters of the obtained phases are quite similar. HgBrI crystallises in the noncentrosymmetric Cmc 2 1 space group, and the experimental intensity of Second Harmonic Generation (SHG) of the powder samples was 1.4 times stronger than that of potassium titanyl phosphate (KTiOPO 4 ), a common standard material in NLO devices.…”
Section: Introductionmentioning
confidence: 86%